Nano metal–organic framework (NMOF)-based strategies for multiplexed microRNA detection in solution and living cancer cells. Issue 5 (17th December 2014) - Wu, Yafeng; Han, Jianyu; Xue, Peng; Xu, Rong; Kang, Yuejun
Abstract : The PNA-NMOF sensor enables quantitative in situ detection and monitoring of spatiotemporal changes of multiple miRNA expression levels in living cells. Abstract : MiRNAs are an emerging type of biomarker for diagnostics and prognostics. A reliable sensing strategy that can monitor miRNA expression in living cancer cells would be critical in view of its extensive advantages for fundamental research related to miRNA-associated bioprocesses and biomedical applications. Conventional miRNA sensing methods include northern blot, microarrays and real-time quantitative PCR. However, none of them is able to monitor miRNA levels expressed in living cancer cells in a real-time fashion. Some fluorescennt biosensors developed recently from carbon nanomaterials, such as single-walled carbon nanotubes (SWNTs), graphene oxide (GO), and carbon nanoparticles, have been successfully used for assaying miRNA in vitro ; however the preparation processes are often expensive, complicated and time-consuming, which have motivated the research on other substitute and novel materials. Herein we present a novel sensing strategy based on peptide nucleic acid (PNA) probes labeled with fluorophores and conjugated with an NMOF vehicle to monitor multiplexed miRNAs in living cancer cells. The NMOF works as a fluorescence quencher of the labelled PNA that is firmly bound with the metal center. In the presence of a target miRNA, PNA is hybridized and released from the NMOF leading to the recovery of fluorescence. This miRNA sensor not only enables the quantitative and highly specific detection of multiplexed miRNAs in living cancer cells, but it also allows the precise and in situ monitoring of the spatiotemporal changes of miRNA expression.